Civil liability provisions for torts of board members in a joint-stock company - Abbas Ziad Kamel Al-Saadi (International Journal of Law Research and Studies, 2026)
The joint-stock company is the ideal model for capital companies and has an integrated organization of a collective nature. It occupies a distinguished position in the economic fabric and contributes to revitalizing economic activity and development. Commercial companies represent the basic sector of any country's economy, as they are one of the components of economic activity. Joint-stock companies have witnessed remarkable development as a result of the growth in the volume of trade exchange. yueabirun ean aradatihim, wayuafiq ealayhim almusahimun wayunazimuha alqanun.Therefore, it is necessary to monitor and control the bodies entrusted with managing the company. The responsibility of the shareholders is limited, and they are responsible for the company’s debts up to the nominal value of the shares. In addition, the members of the board Based on the foregoing, there are two theories that define the legal status of board members: contract and law. The first considers board members to be bound to the company by an agency contract. The legal theory, however, considers board members to be bound by a legal relationship as a body or member of the company, not as its agent. Therefore, the liability of board members is divided between civil (contractual) liability in the event of breach of a contractual obligation (the company's articles of association), and tortious liability in the event of breach of a legal obligation (the company law) that governs it. This liability arises if a causal link exists between the board members' error and the harm suffered by the company, society, shareholders, and third parties.of directors express their will, and the shareholders approve them, and it is regulated by law.Furthermore, the Iraqi Companies Law No. 21  of 1997 (as amended) imposes strict civil liability on members of the boards of directors of joint-stock companies, holding them jointly liable to the company, shareholders, and third parties for management errors that violate the law or the company's bylaws. Members are obligated to exercise the care of a "reasonable person" in managing the company's interests.In fact, this company is managed by three bodies: the General Assembly, the Board of Directors, and the Auditors. The Board of Directors is considered the brains behind the company's management and serves as the compass guiding the company towards prosperity and excellence. It is the apex of the administrative pyramid within the company. Despite the existence of the General Assembly, which manages the company and has supreme authority and legal sovereignty, the Iraqi legislator, like other comparative laws, has paid attention to the Board of Directors, outlining a set of functions that the company's management must undertake through its Board of Directors, which is considered the embodiment of the company. It also manages and supervises the company and sets its general policy.
Keywords: Joint-Stock Company; Board Members; Capital Companies; General Assembly; Contractual Liability; Tort Liability; Joint Liability